Partnerskap på like premisser? : Styringsforventninger og institusjonelle praksiser sett fra lærerutdanningens perspektiv - Nilsen, Gaute Rydland; Helstad, Kristin (Nordic Journal of Comparative and International Education (NJCIE), 2023)
‘Partnership’ is used as a collective term for cooperation on competence development between teacher education institutions and schools and is intended to lead to mutual learning. This article deals with experiences with partnerships from the teacher education`s point of view. The data material consists of interviews with teacher educators and leaders in teacher education institutions. The findings show that the staff members have many positive experiences, but they problematize certain organizational and steering challenges. They point out that it is demanding to share knowledge internally, and that research is somewhat connected to the work. They experience that the partnership primarily takes place on the school's premises, which may be related to the fact that steering expectations are directed at the teacher training programs and not at the schools. The study reveals differences in institutional practices, such as how the work is organized at a larger and a smaller teacher training institution, and whether the work is experienced as an individual or a collective project. The study shows that partnership is a complex phenomenon that shapes political and organizational conditions.